Hexavalent Chromate Reductase Activity in Cell Free Extracts of Penicillium sp. - Damaris L. Arévalo-Rangel; Juan F. Cárdenas-González; Víctor M. Martínez-Juárez; Ismael Acosta-Rodríguez (Bioinorganic Chemistry and Applications)
A chromium-resistant fungus isolated from contaminated air with industrial vapors can be used for reducing toxic Cr(VI) to Cr(III). This study analyzes in vitro reduction of hexavalent chromium using cell free extract(s) of the fungus that was characterized based on optimal temperature, pH, use of electron donors, metal ions and initial Cr(VI) concentration in the reaction mixture. This showed the highest activity at 37°C and pH 7.0; there is an increase in Cr(VI) reductase activity with addition of NADH as an electron donor, and it was highly inhibited by Hg2+, Ca2+ and Mg2+, and azide, EDTA, and KCN.